Implementasi Algoritma Simulated Annealing (SA) dalam Steganografi Discrete Cosine Transform (DCT) - Putra, I Nyoman Dwi Pradnyana; Astawa, I Gede Santi; Suhartana, I Ketut Gede; Giri, Gst. Ayu Vida Mastrika (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024DO - 10.24843/JLK.2024.v13.i02.p17, 2025)
Maintaining confidential data security is very important in an era of rapid technological developments. One method used for this purpose is steganography, which is a technique that allows the hiding of sensitive messages in other media without the knowledge of unauthorized parties. In this context, the Discrete Cosine Transform (DCT) method is used to insert messages into the essential frequency components of the media, such as images. However, the use of DCT can damage image quality, and this is why optimization is necessary. In this research, the Simulated Annealing (SA) algorithm is applied as optimization in DCT steganography. The goal is to find the optimal parameter configuration that can maintain the quality of the steganography image while storing the message efficiently. This research uses 6 RGB and grayscale images each and 3 messages with different capacities. Evaluation is carried out by measuring the Peak Signal-to-Noise Ratio (PSNR) and Computational Cost values. This test obtained good results seen from the PSNR value with the highest value of 57,885 dB for RGB images and 58,402 dB for grayscale images, however testing the insertion process time had an influence on the SA algorithm which required quite a long computing time with 16 seconds for the insertion process. It is hoped that the results of this research will provide additional insight into the development of better and more effective information hiding techniques.